2008
DOI: 10.1007/s12011-008-8302-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and Gender on Al, B, Ba, Ca, Cu, Fe, K, Li, Mg, Mn, Na, P, S, Sr, V, and Zn Contents in Rib Bone of Healthy Humans

Abstract: The effect of age and gender on major, minor, and trace element contents in the intact rib bone of 80 relatively healthy 15-55-year-old women and men was investigated. Contents or upper limit of contents of 16 chemical elements in the rib bone were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). Mean values (M +/- SEpsilonMu) for the mass fraction of Ba, Ca, Cu, Fe, K, Li, Mg, Na, P, S, Sr, and Zn (milligram per kilogram of dry bone) were as follows: 2.54 +/- 0.16, 171,400 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…Women’s tendency to a greater accumulation of Cd in comparison with men (0.06 vs. 0.04 mg/kg), which is often quoted in literature [28, 30, 46], was not confirmed. The content of Cd indicated by Lanocha-Arendarczyk et al [31] was higher than our results (0.05 vs. 0.016 mg/kg).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Women’s tendency to a greater accumulation of Cd in comparison with men (0.06 vs. 0.04 mg/kg), which is often quoted in literature [28, 30, 46], was not confirmed. The content of Cd indicated by Lanocha-Arendarczyk et al [31] was higher than our results (0.05 vs. 0.016 mg/kg).…”
Section: Discussionmentioning
confidence: 77%
“…Research on the content of trace elements and components of the bone tissue concern mainly the hip joint [15, 2025], vertebrae [26, 27] and ribs [28–31]. In contrast, research on the knee joint is quite rare [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that higher Ca, Cl, K, Mg, Mn, Na, and Sr mass fractions were typical of female femoral neck compared with male femoral neck (Table 5). Elevated levels of Ca, Mg, and P in the bone tissue of women compared with men can be attributed to physiological characteristics of the female body related to reproduction [34]. A high content of Sr in the bones of women is likely due to differences in the ratio of nutrition foods of animal and plant origin [34].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of Ca, Mg, and P in the bone tissue of women compared with men can be attributed to physiological characteristics of the female body related to reproduction [34]. A high content of Sr in the bones of women is likely due to differences in the ratio of nutrition foods of animal and plant origin [34]. Usually, women in the Russian Central European region consume more plant foods, which is the main supplier of Sr in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…25 In other bone tissues, e.g., the ribs, iron content was 140 mg/kg, a few times higher than in our study. 26 Subsequent findings reported by Scancar et al confirm the correlation between iron content and the type of bone tissue, e.g., in the iliac crest it was 100-300 mg/kg and, as shown by Takata et al, in the cancellous bone of the ribs it was 377 µg/g. [27][28] Iron concentration in the knee joint is a few times lower than in the hip joint.…”
Section: Discussionmentioning
confidence: 75%